Men with negative results of guaiac-based fecal occult blood test have higher prevalences of colorectal neoplasms than women with positive results - Brenner, Hermann; Hoffmeister, Michael; Birkner, Berndt; Stock, Christian (International journal of cancer, 2014)
Guaiac-based fecal occult blood tests (gFOBTs) are the most commonly applied tests for colorectal cancer screening globally but have relatively poor sensitivity to detect colorectal neoplasms. Men have higher prevalences of colorectal neoplasms than women. In case of a positive gFOBT result, participants are referred to colonoscopy, independent of sex. To assess performance of gFOBT in routine screening practice, we assessed age and sex specific prevalences (age groups: 55-59, 60-64, 65-69 and 70-74) of colorectal neoplasms in 182,956 women and men undergoing colonoscopy for primary screening and in 20,884 women and men undergoing colonoscopy to follow-up a positive gFOBT in Bavaria, Germany, in 2007-2009. We conducted model calculations to estimate prevalences among gFOBT negative individuals. Analogous model calculations were performed for women and men tested positive or negative with fecal immunochemical tests. In all age groups (55-59, 60-64, 65-69 and 70-74 years), men undergoing colonoscopy for primary screening had substantially higher prevalences of any colorectal neoplasms and essentially the same prevalences of advanced colorectal neoplasms compared to women undergoing colonoscopy to follow-up a positive gFOBT. Model calculations suggest that men with negative gFOBT likewise have substantially higher prevalences of colorectal neoplasms than gFOBT positive women in each age group. Model calculations further indicate that no such sex paradoxon occurs, and a much clearer risk stratification can be achieved with fecal immunochemical tests. Our findings underline need to move forward from and overcome shortcomings of gFOBT-based colorectal cancer screening.